2017
DOI: 10.1016/j.celrep.2017.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-Selective Sensitivity to Synchronous Cell Death following Modulation of the Amino Acid Nutrient Cystine

Abstract: SummaryCancer cells reprogram their metabolism, altering both uptake and utilization of extracellular nutrients. We individually depleted amino acid nutrients from isogenic cells expressing commonly activated oncogenes to identify correspondences between nutrient supply and viability. In HME (human mammary epithelial) cells, deprivation of cystine led to increased cell death in cells expressing an activated epidermal growth factor receptor (EGFR) mutant. Cell death occurred via synchronous ferroptosis, with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(167 citation statements)
references
References 38 publications
11
156
0
Order By: Relevance
“…One agent that can trigger ferroptosis in xenograft tumors in vivo are engineered nanoparticles that deliver high concentrations of iron into the cell . Enzymatic depletion of plasma cysteine and cystine using an engineered enzyme, cyst(e)inase, can also reduce tumor growth in various xenograft models of cancer in mice, but does not result in regressions . Whether these two agents cause GPX4 inactivation and how lipid peroxidation is affected at the molecular level are not clear.…”
Section: Gpx4 Lipid Peroxidation and Ferroptosis In Development Andmentioning
confidence: 99%
“…One agent that can trigger ferroptosis in xenograft tumors in vivo are engineered nanoparticles that deliver high concentrations of iron into the cell . Enzymatic depletion of plasma cysteine and cystine using an engineered enzyme, cyst(e)inase, can also reduce tumor growth in various xenograft models of cancer in mice, but does not result in regressions . Whether these two agents cause GPX4 inactivation and how lipid peroxidation is affected at the molecular level are not clear.…”
Section: Gpx4 Lipid Peroxidation and Ferroptosis In Development Andmentioning
confidence: 99%
“…Recent studies have indicated that therapy-resistant and mesenchymal tumor cells, two features seen in the recurrent tumor cells, become more sensitive to cell death induced by cystine deprivation 17, 39 . Cystine is imported into mammalian cells in exchange of the export of glutamate via the xCT transporter 40 , which can be blocked by xCT inhibitors, such as the erastin or sulfasalazine 41, 42, 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of ferroptosis is potential to facilitate sorafenib (an EGFR inhibitor) resistance to cancer cells [23,32]. Previous study has identi ed a potential therapeutic bene t of blocking EGFR with ge tinib in basal-like subtypes of TNBC in vitro [21]).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid ROS increases after suppression of GPX4 [32]. Elimination of ROS sensitizes the BC cells to ge tinib [41].…”
Section: Discussionmentioning
confidence: 99%